SREBP modulates the NADP+/NADPH cycle to control night sleep in Drosophila - Mariano, Vittoria; Kanellopoulos, Alexandros K.; Aiello, Giuseppe; Lo, Adrian C.; Legius, Eric; Achsel, Tilmann; Bagni, Claudia (Nature communications, 2023)
Sleep behavior is conserved throughout evolution, and sleep disturbances are a frequent comorbidity of neuropsychiatric disorders. However, the molecular basis underlying sleep dysfunctions in neurological diseases remains elusive. Using a model for neurodevelopmental disorders (NDDs), the Drosophila Cytoplasmic FMR1 interacting protein haploinsufficiency ( Cyfip 85.1/ + ), we identify a mechanism modulating sleep homeostasis. We show that increased activity of the sterol regulatory element-binding protein (SREBP) in Cyfip 85.1/ + flies induces an increase in the transcription of wakefulness-associated genes, such as the malic enzyme ( Men ), causing a disturbance in the daily NADP + /NADPH ratio oscillations and reducing sleep pressure at the night-time onset. Reduction in SREBP or Men activity in Cyfip 85.1/ + flies enhances the NADP + /NADPH ratio and rescues the sleep deficits, indicating that SREBP and Men are causative for the sleep deficits in Cyfip heterozygous flies. This work suggests modulation of the SREBP metabolic axis as a new avenue worth exploring for its therapeutic potential in sleep disorders. Mechanisms underlying sleep dysfunctions in neurodevelopmental disorders remain elusive. Here, authors use a fly model for the CYFIP haploinsufficiency to show that increased SREBP activity impairs the NADP+/NADPH homeostasis inducing sleep deficits.